2023
DOI: 10.3847/psj/acde80
|View full text |Cite
|
Sign up to set email alerts
|

A Past Episode of Rapid Tidal Evolution of Enceladus?

Abstract: Saturn possesses a dynamically rich system containing numerous moons and impressive rings. Whether the rings of Saturn are much younger than the planet itself has been a long-standing open question; more recently a young age has been proposed for some moons. The recent detection of the fast orbital evolution of Rhea and Titan strongly suggests a highly frequency-dependent tidal response of Saturn, possibly through the excitation of inertial waves within the planet’s convective envelope. Here we show that reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…(2021) concluded that hydrogenotrophic methanogenesis still appears to be the metabolism with the highest energy yield and biomass potential. If Enceladus is younger than once thought (Ćuk & Moutamid, 2023; Ćuk et al., 2016; though see also Nimmo et al., 2023) and/or life is in the early stages of evolution, metabolic inefficiencies may explain some of the high Gibbs free energies inferred. Finally, spatial constraints (e.g., restricted space for a habitat on the seafloor) could limit access to H 2 despite it being readily available in solution, particularly if the ocean plume is rotationally controlled and spatially isolated to a column during transit to the ice layer (e.g., Choblet et al., 2017; Schoenfeld et al., 2023), though wider mixing of seawater with HF and longer timescales of vertical transport have been proposed (e.g., Kang et al., 2022).…”
Section: Discussionmentioning
confidence: 98%
“…(2021) concluded that hydrogenotrophic methanogenesis still appears to be the metabolism with the highest energy yield and biomass potential. If Enceladus is younger than once thought (Ćuk & Moutamid, 2023; Ćuk et al., 2016; though see also Nimmo et al., 2023) and/or life is in the early stages of evolution, metabolic inefficiencies may explain some of the high Gibbs free energies inferred. Finally, spatial constraints (e.g., restricted space for a habitat on the seafloor) could limit access to H 2 despite it being readily available in solution, particularly if the ocean plume is rotationally controlled and spatially isolated to a column during transit to the ice layer (e.g., Choblet et al., 2017; Schoenfeld et al., 2023), though wider mixing of seawater with HF and longer timescales of vertical transport have been proposed (e.g., Kang et al., 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Further discussion on the orbital constraints may be found in the articles by Ćuk et al. ( this collection ) and the paper by Ćuk and El Moutamid ( 2023 ).…”
Section: Evolution Of Dissipationmentioning
confidence: 98%
“… 2018 ; Lainey et al. 2020 ; Ćuk and El Moutamid 2023 ), including the article by Fuller et al. ( this collection ).…”
Section: Evolution Of Dissipationmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the Q of Uranus at the time of tidal heating may have been a short-lived phenomenon and not representative of the longer-term value. One way of achieving this effect, which was recently suggested for Rhea and Enceladus by Ćuk & El Moutamid (2023), is to have the satellite pass through a resonant mode with the planet but not get locked to that resonance. To be effective in driving tidal heating, the satellite would have to have been in an MMR at the time of modecrossing.…”
Section: Nonequilibrium Tidal Heatingmentioning
confidence: 99%